Children of the state : stories of survival and hope in the juvenile justice system - Hobbs, Jeff, 1980- (Scribner, an imprint of Simon & Schuster, Inc., 2023)
"Very little has been written about juvenile justice. In the greater consciousness, the word "justice" in this context has been leeched of meaning; it just signifies prison for kids. But to those living and working in various capacities within that system, the word "justice" holds a sepulchral gravity. In Children of the State, bestselling author of The Short and Tragic Life of Robert Peace Jeff Hobbs presents three different true stories that show the day-to-day life and the existential challenges faced by those living and working in juvenile programs: educators, counselors, administrators, and-most importantly--children. While serving a year-long detention in Wilmington, DE--perennially one of the violent crime capitols of America--a bright but stunted young man considers the benefits and also the immense costs of striving for college acceptance while imprisoned. A career juvenile hall English Language Arts teacher struggles to align the small moments of wonder in her work alongside its overall statistical futility, all while the city government presumes to design a new juvenile system without cinderblocks--and possibly without those teaching in the current system. A territorial fistfight in Paterson, NJ is characterized by the media as a hate crime, and the boy held accountable for that crime seeks redemption and friendship in a rigorous Life & Professional Skills class in lower Manhattan. These stories are followed to their knotty conclusions in triptych form. In chronicling the work of this constellation of people trying to accomplish good work in abjectly horrible systems and circumstances, Children of the State asks: What should society do with young people who have made terrible decisions? For many kids, a woeful mistake made at age thirteen or fourteen--often as a result of external factors bearing upon a biologically immature brain--will resonate through the rest of their lives, making high school difficult, college nearly impossible, and a middle class life a foolish fantasy. To observe these missteps and raw challenges and small triumphs from shoulder height, through the experiences of thinking, feeling, poignant young people, is to be moved to consider altering the fixed narrative currently laid out of them. As Hobbs demonstrates in piercing, vivid prose: No one so young should ever be considered irredeemable"--